Digital Constitutionalism in Europe Reframing Rights and Powers in the Algorithmic Society - De Gregorio, Giovanni (Social Sciences, 2022)
This book provides the first study on digital constitutionalism in Europe. The research explains the European constitutional reaction to the challenges of digital capitalism while exploring a normative perspective to protect fundamental rights and democracy in the algorithmic society based on the path of European digital constitutionalism.